2016
DOI: 10.1080/21655979.2016.1197712
|View full text |Cite
|
Sign up to set email alerts
|

Local deformation for soft tissue simulation

Abstract: This paper presents a new methodology to localize the deformation range to improve the computational efficiency for soft tissue simulation. This methodology identifies the local deformation range from the stress distribution in soft tissues due to an external force. A stress estimation method is used based on elastic theory to estimate the stress in soft tissues according to a depth from the contact surface. The proposed methodology can be used with both mass-spring and finite element modeling approaches for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…22 Additionally, the abdominal tissue layers naturally have some local strain due to muscle contractions or mechanical loading, but the low-level electrical stimulation should not induce harmful local strains. 26 Future studies would be required to determine any deformations created in the mesh due to mechanical loading of the piezo material via ultrasound waves.…”
Section: Discussionmentioning
confidence: 99%
“…22 Additionally, the abdominal tissue layers naturally have some local strain due to muscle contractions or mechanical loading, but the low-level electrical stimulation should not induce harmful local strains. 26 Future studies would be required to determine any deformations created in the mesh due to mechanical loading of the piezo material via ultrasound waves.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the determination of the penetration depth does not consider material properties. Omar et al [38] reported a local deformation method based on MSM. Based on elastic theory, this method estimates the stress distribution in soft tissues according to a depth from the contact surface subject to an external load.…”
Section: ) Mass-spring Modelmentioning
confidence: 99%
“…Stamatia et al, 32 proposes tissue deformation recovery by providing useful feedback on instrument forces exerted on the tissue. Nadzeri et al, 33 focuses on soft tissue simulation in real time using new local deformation methodology. This method evaluates the deformation range using stress evaluation method based on elastic theory.…”
Section: Volumetricmentioning
confidence: 99%